Analisa Kondisi Sumber Daya Manusia Lintas Generasi pada Era Revolusi Industri 4.0 di Indonesia: Tinjauan Literatur - Nopi Hidayat; Musa Hubeis; Anggraini Sukmawati; Eriyatno; Bintang Akbar MB (Jurnal Jaminan Kesehatan Nasional, 2022)
Changes in digitalization and automation show that a country has entered the Industrial Revolution Era 4.0. In its history, the Industrial Revolution has always brought many transformations, including a shift in the function of Human Resources (HR) to machines. Basically the main goal of HR management is to ensure that the organization has the appropriate HR knowledge and skills in the present and future, including changing jobs with the necessary competencies in the right positions. This study helps provide an understanding of cross-generational HR management in the Industrial Revolution 4.0 Era. Talent Management is the key to the challenges in the Industrial Revolution Era 4.0. This study uses literature studies obtained from reference reading sources related to the similarity of human resource conditions in Western countries and Indonesia across generations. It was found that there were similarities in the occurrence of historical phenomena in American, European countries including Indonesia that affected the Baby Boomers Generation, X and Y. The similarity of ways of working, mindset and values in each generation are the advantages of Talent Management in preparing the right competencies in facing the Industrial Revolution Era 4.0.